Detection of the WNT/Beta-Catenin Signaling Activity by Using Immunocytochemical Technique in Cervical Smears - Dönmez, Hanife Güler; Demirezen, Şayeste; Beksaç, Sinan (Gynecology Obstetrics & Reproductive Medicine, 2013)
OBJECTIVES: The Wnt/β-catenin signaling pathway controls cell fate and homeostasis of embryonic and adult tissues. The aim of the study is to evaluate the activity of Wnt/β-catenin signaling in cervical smears by using immunocytochemistry. STUDY DESIGN: Cervical smears taken from 200 patients were examined in terms of immunostaining of β-catenin. The membranous staining with moderate (++) or strong (+++) cytoplasmic and/or nuclear staining was scored positive for signaling activity. RESULTS: Positive Wnt/β-catenin signaling was found in 21 of 200 cases (10.5%). The nucleus was not found to be positive in any of the cells. However, some nuclear membranes were positive. In addition, when signaling was active, the membranous expression of β-catenin was observed to increase by a statistically significant amount epithelial cells (p<0.05). CONCLUSION: Our data indicates that immunocytochemical techniques can be used to detect the activity of the Wnt/β-catenin signaling pathway in routine cervical smears.